Longitudinality in Primary Health Care: a bibliometric study (Research, Society and Development, 2022)
Objective: This work aims to describe the national and international scientific production that addresses the longitudinality attribute in Primary Health Care. Methodology: This study is based on a bibliometric, quantitative study prepared in June 2021 in the Web of Science database. Result and Discussion Result and Discussion: 58 publications were collected and analyzed in the period from 1997 to 2021, there is the dissemination of the theme especially from the year 2010, with emphasis on Brazil as a place of affiliation of most studies and the weak network of collaboration between topic authors. Conclusion: Bibliometrics indicates that despite the resurgence of research related to the subject in question, it is still necessary to encourage research to know the different locoregional specificities and thus strengthen the attribute in Primary Health Care.